Implementing a robust and accurate pedometer on mobile phone - Yoong, Wei Fah (2017)
Step detection is a process that will determine if a footstep occurs. Step counters are gaining popularity in everyday exercises, through measuring physical activities as well as being part of navigation systems. Accelerometer is a sensor in which it exists in almost every smart-phone devices which are widely used around the world, and it is used to measure acceleration forces in which may be static like the continuous force of gravity or dynamic to sense movement or vibrations. Based on initial data analysis and research, it is shown that most of the time, steps are miscalculated either via false positive or missing step count. It is important to develop an accurate and robust pedometer that will be able to record all step count accurately as well as decreasing the amount of false positive. This project will be focusing on developing a Pedometer application on an Android platform, utilizing the sensor data collected from the in-built accelerometer.